Distribution of Endogenous NO Regulates Early Gravitropic Response and PIN2 Localization in Arabidopsis Roots - París, Ramiro; Vazquez, María M.; Graziano, Magdalena; Terrile, María C.; Miller, Nathan D.; Spalding, Edgar P.; Otegui, Marisa S.; Casalongué, Claudia A. (Frontiers in Plant Science, 2018)
High-resolution and automated image analysis of individual roots demonstrated that endogenous nitric oxide (NO) contributes significantly to gravitropism of Arabidopsis roots. Lowering of endogenous NO concentrations strongly reduced and even reversed gravitropism, resulting in upward bending, without affecting root growth rate. Notably, the asymmetric accumulation of NO along the upper and lower sides of roots correlated with a positive gravitropic response. Detection of NO by the specific DAF-FM DA fluorescent probe revealed that NO was higher at the lower side of horizontally-oriented roots returning to initial values 2 h after the onset of gravistimulation. We demonstrate that NO promotes plasma membrane re-localization of PIN2 in epidermal cells, which is required during the early root gravitropic response. The dynamic and asymmetric localization of both auxin and NO is critical to regulate auxin polar transport during gravitropism. Our results collectively suggest that, although auxin and NO crosstalk occurs at different levels of regulation, they converge in the regulation of PIN2 membrane trafficking in gravistimulated roots, supporting the notion that a temporally and spatially coordinated network of signal molecules could participate in the early phases of auxin polar transport during gravitropism.